A stability-based target displacement for direct displacement-based design of bridge Piers - Suarez Chacon, V. (2017)
P-? effects can cause instability if they are not properly accounted for during the design of bridge piers and other structures. When a bridge pier is designed with the Direct Displacement-Based Design Method, P-? effects are evaluated at the end of the design process and compared to the flexural strength of the pier to find a stability index. If the stability index exceeds the specified value, the design must be repeated, iteratively reducing the target design displacement. This article presents a model that when used at the beginning of design (without knowledge of strength) allows the estimation of the maximum lateral displacement that a bridge pier can sustain without exceeding the specified value of the stability index, therefore eliminating the need for iteration. The examples that are presented prove that the model is accurate and very useful for design of extended pile bents. Copyright © A. S. Elnashai & N. N. Ambraseys.